2022
DOI: 10.1038/s41598-022-15797-0
|View full text |Cite|
|
Sign up to set email alerts
|

Melting enhancement of PCM in a finned tube latent heat thermal energy storage

Abstract: The current paper discusses the numerical simulation results of the NePCM melting process inside an annulus thermal storage system. The TES system consists of a wavy shell wall and a cylindrical tube equipped with three fins. The enthalpy-porosity method was utilized to address the transient behavior of the melting process, while the Galerkin FE technique was used to solve the system governing equations. The results were displayed for different inner tube positions (right-left–up and down), inner cylinder rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The simplest one is, of course, increasing the heat transfer surface. This is achieved, for example, by the use of extended surfaces, and finned surfaces, e.g., [4,5]. Another way is to use inserts immersed in PCM with a large surface area and high thermal conductivity, such as carbon brushes [6,7], metal foams [8,9], porous materials [10][11][12], metal rings [13,14], or metal matrices [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The simplest one is, of course, increasing the heat transfer surface. This is achieved, for example, by the use of extended surfaces, and finned surfaces, e.g., [4,5]. Another way is to use inserts immersed in PCM with a large surface area and high thermal conductivity, such as carbon brushes [6,7], metal foams [8,9], porous materials [10][11][12], metal rings [13,14], or metal matrices [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al (2020) studied the effects of nanoparticles dispersed into paraffin wax, showing that nanoparticle application enhances the solidification procedure and diminishes entropy formation. Ahmed et al (2022) investigated different geometry modifications and nanoparticle addition techniques in a PCM container during melting. They performed a numerical simulation on a wavy circular cylinder containing nano-additives and showed that the melting rate augments with increasing nanoparticle concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The current research focus is on improving the thermal conductivity of PCMs and strengthening their heat transfer capacity. The commonly used methods include adopting fin-tubes [2,3] and PCM microcapsules [4,5], adding metal rings and graphite [6,7], filling PCM into porous matrixes such as metal foams [8][9][10], and so on.…”
Section: Introductionmentioning
confidence: 99%